2021
DOI: 10.1192/bji.2021.53
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol, captagon and khat use in the Eastern Mediterranean Region: opening Pandora's box

Abstract: As defined by the World Health Organization, the Eastern Mediterranean Region (EMR), given its special geopolitical situation and internal/external conflicts, faces an increase in illegal activities such as drug production and trafficking, highlighting the need for a comprehensive understanding of the substance use situation. On the basis of a review of published papers between 2015 and 2021 we briefly review substance use in the EMR with special focus on the emerging drugs pertinent to this region, namely tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The drugs of abuse used in the EMR differ from the drugs abused in Western Europe and the United States. The EMR is defined by the World Health Organization (WHO) as encompassing 22 members with about 700 million inhabitants [ 8 ], many of these countries are facing increasing rates of use of other illicit substances, including but not limited to the use of captagon [ 9 ]. The EMR is a vast and heterogeneous region, home to economically devastated nations, such as Yemen and Somalia, as well as some of the wealthiest nations on earth, such as the United Arab Emirates and Qatar.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The drugs of abuse used in the EMR differ from the drugs abused in Western Europe and the United States. The EMR is defined by the World Health Organization (WHO) as encompassing 22 members with about 700 million inhabitants [ 8 ], many of these countries are facing increasing rates of use of other illicit substances, including but not limited to the use of captagon [ 9 ]. The EMR is a vast and heterogeneous region, home to economically devastated nations, such as Yemen and Somalia, as well as some of the wealthiest nations on earth, such as the United Arab Emirates and Qatar.…”
Section: Reviewmentioning
confidence: 99%
“…Polysubstance drug abuse may be intentional, opportunistic, or unintentional, when a user takes a contaminated product mixed with other substances. Polysubstance abuse is a global trend that occurs in the EMR as well as in other regions [ 9 , 52 ]. However polysubstance abuse in the EMR is more likely to include captagon in the mix than polysubstance cocktails in Western Europe and North America.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is compounded by the long-standing position of this region as one of the largest opium production sites globally. In the second article on our theme, Mohaddes Ardabili et al 3 shed light on patterns of substance use in the region.…”
Section: Substance Use In the Eastern Mediterranean Regionmentioning
confidence: 99%
“…In most African countries, it is easy to obtain in pharmacies without a medical prescription [ 2 ]. In North African countries, a literature review showed that tramadol is the second most used drug by students in Egypt due to its psychoactive properties [ 15 ] and more generally in countries in the Eastern Mediterranean region, including Libya, Morocco, Somalia and Tunisia [ 16 ]. In Central Africa, especially Cameroon, tramadol is used illicitly for its psychoactive properties and to increase work efficiency [ 17 ].…”
Section: Introductionmentioning
confidence: 99%